2020
DOI: 10.1093/sleep/zsaa194
|View full text |Cite
|
Sign up to set email alerts
|

The evening light environment in hospitals can be designed to produce less disruptive effects on the circadian system and improve sleep

Abstract: Study objectives Blue-depleted lighting reduces the disruptive effects of evening artificial light on the circadian system in laboratory experiments, but this has not yet been shown in naturalistic settings. The aim of the current study was to test the effects of residing in an evening blue-depleted light environment (LE) on melatonin levels, sleep, neurocognitive arousal, sleepiness and potential side-effects. Methods The st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
56
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 68 publications
(34 reference statements)
7
56
2
Order By: Relevance
“…Previous works already showed that metamer spectra could be used to affect physiological responses [23,66]. For the practical implementation of metamer spectra, it is essential to use stimuli with a high dynamic in their melanopic radiance at a steady chromaticity target.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous works already showed that metamer spectra could be used to affect physiological responses [23,66]. For the practical implementation of metamer spectra, it is essential to use stimuli with a high dynamic in their melanopic radiance at a steady chromaticity target.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the aspect of saving energy, research is focusing on the implementation of dynamic patterns of light exposure [12], which vary the illumination or the correlated colour temperature (CCT) to support the circadian rhythm [13] or task-related performance [12]. The discovery of intrinsically photosensitive ganglion cells (ipRGCs) [14][15][16][17][18] made clear that besides the image-forming properties of colour and brightness perception [19], the composition of a light spectrum [20] can also affect the human alertness and cognitive performance [6,[21][22][23]. In the outer retina, six subtypes of ipRGCs (M1 to M6) can be distinguished, each with unique morphological, functional and physiological properties projecting to different targets in the brain [24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, photopic illuminance is, compared to light exposure in healthy individuals, usually fairly low during the day and relatively high during the night [30]. This may result in disruptive effects on the circadian system and the sleep-wake cycle [31], which is especially critical for patients with DOC whose arousal levels anyway strongly fluctuate. Beyond this, it is well-known that an impairment of sleep can have detrimental effects on the immune system and the recovery from illness (for a review see [32]).…”
Section: Introductionmentioning
confidence: 99%